SISTEM INFORMASI PENJUALAN KENDARAAN BERMOTOR BERBASIS WEB - Aldyanto, Aldyanto; Gultom, Manorang; Kartono, Kartono (LPPM Universitas Widya Dharma Pontianak, 2024)
This research discusses the importance of web-based motor vehicle sales information systems in supporting the development of the automotive industry in the digital era. With population growth, and economic development driving demand for motor vehicles, the automotive industry faces complex challenges in meeting the needs of modern consumers. This resarch discusses the development and implementation of a web-based application information system designed for motor vehicle sales. The purpose of this system is to create an efficient and user-friendly platform that connects sellers and buyers, streamlining the buying and selling process of motor vehicles. The application includes various features such as user validations, detailed vehicle listings, advanced search and filter capabilities, secure transaction processing, and real-time chat support. Additionally, the system integrates a robust database management system to store and manage vehicle and user data securely.This study integrates understanding of information technology, business, and legal aspects to explore how such information systems can add value to consumers and stakeholders in the automotive supply chain. In this paper, we highlight changes in consumer behavior, transformations in the automotive industry, and data security as key factors influencing the relevance and need for such information systems. The findings of this research are expected to provide valuable insights for the automotive industry and related stakeholders in developing responsive and effective information systems. Keywords: Sales, Sites, Motor, Vehicles, Designing, Web